Welfare Level of Fishermen’s Senangin (Eleutheronema tetradactylum) With Gill Net Catching Tools in Sinaboi District, Rokan Hilir Regency, Riau Province - Kusai Kusai; Trisla Warningsih; Zulkarnain Zulkarnain (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2023)
Senangin fish (Eleutheronema tetradactylum) is one of the products of capture fisheries in Rokan Hilir Regency which has economic value. However, the production of the catches of Senangin fish which tends to decrease from year to year causes the income earned by fishermen to also decrease, thus affecting the welfare of fishermen. Based on this, this study aims to measure the level of welfare of Senangin fishing fishermen in Sinaboi, Rokan Hilir Regency by using a survey method. This research was conducted on March to June 2022. The technique of determining respondents used simple random sampling technique with a total of 24 fishermen with gill net fishing gear. Data analysing used the level of BKKBN family welfare. The results of the study showed that the fishermen of Sengain fish with gill net fishing gear in Sinaboi District were dominated by the Prosperous Family group I (45.83%). Furthermore, the fishermen's family of Happy in the Prosperous Family II group was 37.5%, the Prosperous Family III was 16.67%, and no fishermen were found in the Happy Family group as well as the Prosperous Family III Plus group.